2021
DOI: 10.3390/vaccines9111267
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Breakthrough Infections and Transmission Risk: Real-World Data Analyses from Germany’s Largest Public Health Department (Cologne)

Abstract: Background and Methods: Vaccination is currently considered the most successful strategy for combating the SARS-CoV-2 virus. According to short-term clinical trials, protection against infection is estimated to reach up to 95% after complete vaccination (≥14 days after receipt of all recommended COVID-19 vaccine doses). Nevertheless, infections despite vaccination, so-called breakthrough infections, are documented. Even though they are more likely to have a milder or even asymptomatic course, the assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 23 publications
0
28
0
1
Order By: Relevance
“…It has been reported that elderly people lose vaccine antibodies more quickly and that the vaccine is less effective against variant strains 22 . Furthermore, Hsu et al previously reported that the number of transmissions from unvaccinated controls was three times higher than from fully vaccinated patients 22,23 . In our cohort, the number of cases identified within clusters decreased over, time and only one quarter of newly identified cases caused intra‐facility transmission.…”
Section: Discussionmentioning
confidence: 48%
“…It has been reported that elderly people lose vaccine antibodies more quickly and that the vaccine is less effective against variant strains 22 . Furthermore, Hsu et al previously reported that the number of transmissions from unvaccinated controls was three times higher than from fully vaccinated patients 22,23 . In our cohort, the number of cases identified within clusters decreased over, time and only one quarter of newly identified cases caused intra‐facility transmission.…”
Section: Discussionmentioning
confidence: 48%
“…In Spring 2020, when the data for the current study was collected, vaccination was only offered to adolescents aged 16 years and older ( Government of Canada, 2021 ). Thus, the majority of school staff were interacting with unvaccinated students, who were more likely to transmit COVID-19 than if they were vaccinated ( Hsu et al, 2021 ), which could have been an additional source of anxiety and stress for school staff.…”
Section: Discussionmentioning
confidence: 99%
“…This has mainly concerned the B.1.617.2 (delta) variant that was first identified in India in December 2020 and became dominant in the European Region by June/July 2021 [ 8 ]. A number of post-authorization studies originating from different countries in mid-2021 have shown that despite SARS-CoV-2 evolution, vaccination continues to decrease the risk of contracting the virus [ 2 , 9 , 10 , 11 ], while in the case of breakthrough infection, the risk of severe disease, hospitalization, and death is significantly reduced [ 12 , 13 , 14 , 15 ]. However, SARS-CoV-2, similarly to other respiratory viruses, reveals a strong seasonal pattern in the temperate zone, with infection rates rising in the autumn-winter season [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%